Some Uniqueness Results of the Solutions for Two Kinds of Riccati Equations with Variable Fractional Derivative. (17th January 2022) - Lin, Shi-you; Chen, Li-sha; Li, Bo-yang
Abstract : We mainly discuss the relevant properties of the solution of the Riccati equation in this paper. By virtue of our previous derivation, we will give several uniqueness conclusions that the initial value problems of some kinds of the Riccati equation with variable fractional derivative are solved under certain conditions. Additionally, we also point out an error in the work of Kashkari and Syam and correct it.